Starch (Tapioca) to carbon dots: an efficient green approach to an on-off-on photoluminescence probe for fluoride ion sensing - Basu, Aniruddha; Suryawanshi, Anil; Kumawat, Begraj; Dandia, Anshu; Guin, Debanjan; Ogale, Satishchandra B. (Analyst, 2015)
Photoluminescent carbon dots of 4-5 nm size were prepared from starch (Tapioca Sago) through a solution method under mild conditions. The as-prepared carbon dots were used as photoluminescence probes for highly anion selective fluoride ion detection in aqueous solutions. A ready-to-use device is also demonstrated.